Quantification of the Seismic Behavior of a Steel Transmission Tower Subjected to Single and Repeated Seismic Excitations Using Vulnerability Function and Collapse Margin Ratio - Kassem M.M.; Beddu S.; Min W.Q.; Tan C.G.; Nazri F.M. (MDPI, 2023)
Transmission towers are a vital lifeline for modern living and are crucial structures that must remain operational even after a seismic event. However, the towers are largely designed to withstand the effects of wind alone and not earthquakes, and the seismic influences on tower design and construction have hitherto been ignored. The purpose of this study was to evaluate the seismic performance of a latticed steel transmission tower-line system that is subjected to a variety of seismic situations (Far-Field, Near-Field and Repeated Earthquakes) using probabilistic vulnerability functions and Collapse Margin Ratios in accordance with FEMA-P695. Nonlinear Time History Analyses were performed by incorporating an array of 36 strong ground motions to develop the Incremental Dynamic Analysis and to generate the fragility functions for three performance limit states as referenced in FEMA 356. The results showed that the single event seismic performance of the tower is better than its performance after multiple ground motions owing to aftershock impact, while near-field excitations led to greater susceptibility and fragility than far-field scenarios. Thus, near-field ground motion is more harmful to the tower and could result in its failure or collapse with only a small reduction in damage relative to the impact of the aftershock. 2022 by the authors. Licensee MDPI, Basel, Switzerland.